2012
DOI: 10.1016/j.ydbio.2012.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase 9/gelatinase B is required for neural crest cell migration

Abstract: This study determined the role of MMP9/gelatinase B during the migration onset of Neural Crest Cells (NCC) in avian embryos. NCC are neuroepithelial progenitors that convert into mesenchyme and migrate along defined paths throughout the embryo. To engage in migration, NCC loose cell contacts, detach from the neural tube and invade the surrounding environment. Multiple signals and transcription factors that regulate these events have been identified. Nevertheless, little is known regarding effectors that act do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(86 citation statements)
references
References 102 publications
6
79
1
Order By: Relevance
“…To achieve metastasis, a tumor cell must disrupt cell-cell and cell-extracellular matrix contacts, migrate through stromal tissue, invade the basement membrane, and enter/exit the blood stream. These steps are primarily accomplished by the activity of the MMP family of enzymes (Singh et al, 2012;Monsonego-Ornan et al, 2012). However, we did not find that MMP-2 had prognostic importance in the multivariate Cox proportional hazard regression analysis.…”
Section: Discussioncontrasting
confidence: 75%
“…To achieve metastasis, a tumor cell must disrupt cell-cell and cell-extracellular matrix contacts, migrate through stromal tissue, invade the basement membrane, and enter/exit the blood stream. These steps are primarily accomplished by the activity of the MMP family of enzymes (Singh et al, 2012;Monsonego-Ornan et al, 2012). However, we did not find that MMP-2 had prognostic importance in the multivariate Cox proportional hazard regression analysis.…”
Section: Discussioncontrasting
confidence: 75%
“…On the other hand, mmp-9 transcript was detected in all chick embryo NC cells and in the regions through which they migrate (Monsonego-Ornan et al, 2012). Loss of MMP-9 function by using either an MMP-9-selective inhibitor or an antisense morpholino decreased NC cell delamination and migration both in vitro and in vivo at multiple stages in this study, while addition of MMP-9 enhanced both delamination and migration.…”
Section: Gelatinasesmentioning
confidence: 50%
“…Among these MMPs, MMP-2 (gelatinase-A) and MMP-9 (gelatinase-B) are mainly involved in cancer metastasis and invasion. They predominantly degrade gelatin and type IV, V, XI and XVI collagen, the major structural component of basement membrane, which appears to be crucial in tumor cell invasion and metastasis (8)(9)(10). A previous study reported that oroxylin A could inhibit migration and invasion of human breast MDA-MB-435 cancer cells via the inhibition of MMP-2 and MMP-9 (11).…”
Section: Introductionmentioning
confidence: 99%